2017
DOI: 10.1123/jsr.2015-0134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Athletic Identity and Beliefs About Rehabilitation Overadherence in College Athletes

Abstract: Negative affectivity accounted for a significant but low amount of variance for rehabilitation overadherence, suggesting that athletic trainers should pay attention to personal variables such as athletic identity that might influence the rehabilitation process. Using the knowledge of why athletes adhere to their rehabilitation and what is most important to them about being an athlete, athletic trainers can use appropriate interventions to facilitate proper rehabilitation adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…According to Hughes and Coakley [16], people who self-identify strongly and exclusively as athletes tend to subscribe to the sociocultural "sport ethic" value system that emphasizes the importance of athletes making sacrifices for their sport, accepting risks, and playing through pain and injury. In support of this claim, positive associations have been documented between athletic identity and the tendencies to report playing through pain [17] and over-adhering to sport injury rehabilitation [18]. Further, in a study of male intercollegiate hockey players, athletic identity was found to moderate the association between subjective norms and concussion symptom reporting such that "for any given level of perceived reporting norms, higher athletic identity will result in slightly greater odds of under reporting behavior" [19] (p. 98).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Hughes and Coakley [16], people who self-identify strongly and exclusively as athletes tend to subscribe to the sociocultural "sport ethic" value system that emphasizes the importance of athletes making sacrifices for their sport, accepting risks, and playing through pain and injury. In support of this claim, positive associations have been documented between athletic identity and the tendencies to report playing through pain [17] and over-adhering to sport injury rehabilitation [18]. Further, in a study of male intercollegiate hockey players, athletic identity was found to moderate the association between subjective norms and concussion symptom reporting such that "for any given level of perceived reporting norms, higher athletic identity will result in slightly greater odds of under reporting behavior" [19] (p. 98).…”
Section: Introductionmentioning
confidence: 94%
“…A secondary purpose was to examine the relationship between athletic identity and the concussion retirement number. Based on the theoretical position of Hughes and Coakley [16] and the findings of Weinberg et al [17], Hilliard et al [18], and Kroshus et al [19], it was hypothesized that athletic identity would be positively associated with the concussion retirement number.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes who sustain concussions often experience physical, psychological, and emotional effects (Kroshus, Kubzansky, Goldman, & Austin, 2015; Weinberg, Vernau, & Horn, 2013). These outcomes are further exaggerated by challenges related to their inability to participate in sport, which for some athletes, functions as a significant identity mechanism (Colon, Smith, & Fucillo, 2017; Hilliard, Blom, Hankemeier, & Bolin, 2017; Weinberg et al, 2013). Thus, the concussion recovery process can be frustrating for athletes due to the physical symptoms (e.g., inability to tolerate light), daily routine disruption (e.g., ability to attend school), social isolation from peers, and identity loss (Covassin, Elbin, Beidler, LaFevor, & Kontos, 2017).…”
mentioning
confidence: 99%
“…Feelings of vulnerability and the desire to seek supportive relationships may influence athletes help seeking attitudes in sport (Biddle et al, 2003). Higher levels of perceived athletic identity have also been associated with rehabilitation over-adherence (Hilliard, Blom, Hankemeier, & Bolin, 2016), thus suggesting that athletic identity can influence one's behaviors during injury rehabilitation and ultimately have negative effects on the overall rehabilitation outcomes (Granquist & Brewer, 2013). This study aims to fill the research gaps identified above by investigating whether athletes' attitudes towards athletic trainers and sport psychology consultants differ considering the nature of athletic ability beliefs and previous experiences with the aforementioned professionals.…”
Section: Introductionmentioning
confidence: 99%